2011
DOI: 10.1515/jpem.2011.354
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prevalence of non-classical congenital adrenal hyperplasia with a V281l mutation in patients with premature pubarche

Abstract: We aimed to determine the prevalence and clinical characteristics of non-classical congenital adrenal hyperplasia (NCCAH) with V281L mutation in patients with premature pubarche. An adrenocorticotrophic hormone (ACTH) stimu lation test was performed in 14 of the 159 patients with premature pubarche (PP). Patients whose stimulated 17 α -hydroxyprogesterone (17-OHP) level on the ACTH test was ≥ 10 ng/mL underwent a mutational analysis of the CYP21 gene. NCCAH was defi ned in nine (5.7 % ) patients, all of whom h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
(28 reference statements)
5
3
0
Order By: Relevance
“…However, it is important to exclude NCCAH to warrant the correct treatment and to avoid related medical problems 3,14 . In our cohort, prevalence of NCCAH was 7.6% (7/92), similar to that found in other cohorts with low prevalence of NCCAH 15,16 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is important to exclude NCCAH to warrant the correct treatment and to avoid related medical problems 3,14 . In our cohort, prevalence of NCCAH was 7.6% (7/92), similar to that found in other cohorts with low prevalence of NCCAH 15,16 .…”
Section: Discussionsupporting
confidence: 90%
“…In our prospective study, among the clinical parameters, only accelerated bone age maturation was significantly different in patients with NCCAH, as previously reported 15 . However, obesity is frequently associated with bone age acceleration, and given the strong increase of prevalence of pediatric obesity and, in particular, its association with premature pubertal development, we do not think that this parameter could be useful in clinical practice 20 .…”
Section: Discussionsupporting
confidence: 87%
“…We examined all IPP patients, and the six patients for whom NCAH was diagnosed as the cause of PP, in an effort to identify factors predictive of NCAH development. Most prior studies have proposed that patients with NCAH exhibit accelerated bone-age maturation [23, 2931] and increased basal or stimulated levels of 17-OHP [29, 32, 33]. In the present study, as expected, the basal and stimulated levels of 17-OHP were higher ( P < 0.001), and the bone-age SD was more advanced ( P < 0.05), in children with NCAH.…”
Section: Discussionsupporting
confidence: 83%
“…As found previously, the Q318X mutation was also noted in patients presenting with PCOS [22, 41]. Erdeve et al [23] detected the V281L mutation in all PP patients of a Turkish population and suggested that the condition was caused by this mutation rather than other known mutations. Moreover, it has been reported that the V281L mutation is the most common mutation in Turkish patients with PP, PCOS, and hirsutism [25, 27].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation